2005
DOI: 10.1080/10715760500045855
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants protect the yeastSaccharomyces cerevisiaeagainst hypertonic stress

Abstract: Yeast (Saccharomyces cerevisiae) mutants lacking CuZnSOD have been reported to be hypersensitive to hypertonic media and to show increased oxidative damage. This study demonstrates that hypertonic medium (containing 0.8 M NaCl) increases the generation of superoxide and other reactive species in yeast cells. Other sequelae of exposure to hypertonic medium include oxidation of cellular low-molecular weight thiols and decrease in total antioxidant capacity of cellular extracts. deltasod1 mutant is more sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 18 publications
3
54
1
Order By: Relevance
“…The SOD1Δ strain exhibited high sensitivity to paraquat and methionine auxotrophy (data not shown), that was observed with previously isolated Sod1-lacking mutants (Bilinski et al, 1985;Chang and Kosman, 1990). Osmotic stress also hampers the growth of yeast cells, and the SOD1 mutants are oversensitive to hypertonic medium (e.g., one containing 0.8 M NaCl) (Garay-Arroyo et al, 2003;Koziol et al, 2005). We compared cell growth under aerobic conditions of the SOD1Δ strain with that of wild-type yeast in YPD liquid media containing various concentrations of sorbitol, and also observed growth inhibition of the SOD1Δ strain at high concentrations of sorbitol ( Fig.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…The SOD1Δ strain exhibited high sensitivity to paraquat and methionine auxotrophy (data not shown), that was observed with previously isolated Sod1-lacking mutants (Bilinski et al, 1985;Chang and Kosman, 1990). Osmotic stress also hampers the growth of yeast cells, and the SOD1 mutants are oversensitive to hypertonic medium (e.g., one containing 0.8 M NaCl) (Garay-Arroyo et al, 2003;Koziol et al, 2005). We compared cell growth under aerobic conditions of the SOD1Δ strain with that of wild-type yeast in YPD liquid media containing various concentrations of sorbitol, and also observed growth inhibition of the SOD1Δ strain at high concentrations of sorbitol ( Fig.…”
Section: Resultsmentioning
confidence: 58%
“…This suggests that inactivation of such antioxidants during cultivation is not responsible for the absence of growth restoration in SOD1Δ cells. Koziol et al (2005) established a similar method using another Sod1-deficient strain, and also found that a limited number of antioxidants (AsA and thiols) were able to improve the growth of the cells under hyperosmosis. Other categories of antioxidants, including Trolox, melatonin, and TEMPO, had no effect.…”
Section: Sod1 Sod2mentioning
confidence: 99%
See 2 more Smart Citations
“…Cells have been known to be hypersensitive to hypertonic media and to show an increased oxidative damage (Koziol et al, 2005). In the present study, colon cells encounter multiple stress conditions, such as acetic acid-induced colitis and hyperosmotic stress with intracolonic gel containing Naalginate.…”
Section: In Vivo Studiesmentioning
confidence: 99%